Weed control under integrated nutrient management systems in faba bean (Vicia faba) production in Egypt - El-Metwally,I.M. (2008)
Two field experiments were conducted in two successive seasons, 2005/2006 and 2006/2007, to determine whether management can improve faba bean competitiveness with weeds, thus helping to achieve its yield potential. The experiment included five treatments, composed of organic and mineral fertilizers, alone and mixed at different rates, along with a control and six weed control treatments, including oxadiargyl, prometryn, hand hoeing treatments alone or mixed with the herbicides, and a nonweeded treatment (control).The herbicide treatments were not superior to the two hand-hoeing treatments. Using compost favored growth and yield of faba bean more than of weeds. Adding fertilizer also improved most yield parameters. Application of compost alone or combined with 50 or 100% of the recommended NPK rate improved faba bean growth in terms of net assimilation rate, specific leaf area, and leaf weight ratio as components of relative growth rate. This improvement in growth resulted in increase of seed yield, yield components and protein of faba bean. Faba bean yield performance improved under interactive fertilizer effects and weed control treatments as growth improved, as a result of nutrient release from fertilizers and weed control.